Daily walking habit reduces fasting blood sugar level in newly diagnosed diabetic participants in rural Bangladesh - Subrina Jesmin; Takeru Shima; Naoto Yamaguchi; Farzana Sohael; Adil Maqbool; Arifur Rahman; Masao Moroi; Nobutake Shimojo; Saturo Kawano; Koichi Watanabe; Fumi Takeda; Hideaki Soya (Japanese Society of Physical Fitness and Sports Medicine, 2021)
Diabetes mellitus, a life-threatening non-communicable disease, is now an epidemic-level problem in developed countries, and also prevalent in developing countries, including Bangladesh. Bangladesh has been facing a significant and growing burden of diabetes mellitus handling in recent decades. In the present study, we investigated whether a daily walking intervention could improve the fasting blood sugar level in newly diagnosed diabetes mellitus participants in rural Bangladesh who were not on medication. A rural population of 1,045 people in Bangladesh were screened for diabetes mellitus. One hundred fifty-six people, including 87 diabetes mellitus participants, went through a 5-month daily walking program (twice daily, 1.5 km walking each time). In our initial screening, the prevalence of newly diagnosed diabetes mellitus cases was 8.5% in the rural population. Mean fasting blood sugar level in these new diabetes mellitus cases was 10.0 ± 0.33 mmol/L. After five months of exercise, both the fasting blood sugar and 2h OGTT sugar levels were significantly improved, and no DM (diabetes mellitus) cases were on medication. The current research findings show that a walking program can be a potential lifestyle intervention to combat the diabetes mellitus epidemic in a poor rural context in Bangladesh.